1962
DOI: 10.1126/science.135.3502.439
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of Bacteria

Abstract: A variety of viable and non-viable bacteria became mineralized with hydroxyapatite when implanted in dialysis bags in the peritoneal cavities of rats. The microscopic pattern of mineral deposition appeared analogous to that in the formation of oral calculus. Since nonviable organisms were mineralized at an accelerated rate, bacterial metabolic processes may not be essential for mineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

1963
1963
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 5 publications
1
15
1
Order By: Relevance
“…naedundii and Citron (1945) reported on the alkaline phosphatase activity of species of Actinomyces. Rizzo, Martin, Scott & Mergenhagen (1962) found that the dead organisms of Actinomyces and other bacterial species strongly absorbed calcium phosphate of the animal and deposited it in the form of hydroxyapatite. Also, the high concentration of phosphatase in wound tissue or in histocytes and macrophages (Gomori, 1943;Carranza & Cabrini, 1962) probably plays an important role in tissue infected with Actinomyces.…”
Section: Discussionmentioning
confidence: 99%
“…naedundii and Citron (1945) reported on the alkaline phosphatase activity of species of Actinomyces. Rizzo, Martin, Scott & Mergenhagen (1962) found that the dead organisms of Actinomyces and other bacterial species strongly absorbed calcium phosphate of the animal and deposited it in the form of hydroxyapatite. Also, the high concentration of phosphatase in wound tissue or in histocytes and macrophages (Gomori, 1943;Carranza & Cabrini, 1962) probably plays an important role in tissue infected with Actinomyces.…”
Section: Discussionmentioning
confidence: 99%
“…As to whether the bacteria or the matrix calcifies first, when bacteria calcify to form calculus, is a controversial question. Rizzo et al [22] and TAKAZOE et al [23] reported that formalin-killed bacteria calcified faster than living bacteria. LIE et al [20] observed the calcification of Bacterionema matruchotii in vitro with a transmission electron microscope and found intracellular and extracellular calcifications.…”
Section: Discussionmentioning
confidence: 99%
“…An antimicrobial increases calculus through the dynamics of biofilm petrification leading to cementation. Antimicrobials delay the onset of plaque formation but they also increase the mineralizaton rate of plaque and microorganisms (Rizzo et al, 1962;Sideaway, 1978). While it might take longer to form an initial layer of biofilm with regular antimicrobial use, the layers that form would be encouraged to undergo extensive mineralization.…”
Section: The Importance Of Adhesion/cementation To Calculus Formationmentioning
confidence: 99%